1996
DOI: 10.1190/1.1444058
|View full text |Cite
|
Sign up to set email alerts
|

3-D seismic imaging and seismic attribute analysis of genetic sequences deposited in low‐accommodation conditions

Abstract: A multidisciplinary team, composed of stratigraphers, petrophysicists, reservoir engineers, and geophysicists, studied a portion of Boonsville gas field in the Fort Worth Basin of North‐Central Texas to determine how modern geophysical, geological, and engineering techniques could be combined to understand the mechanisms by which fluvio‐deltaic depositional processes create reservoir compartmentalization in a low‐ to moderate‐accommodation basin. An extensive database involving well logs, cores, production, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The overlying strata were generally lithified, but the sag also affected concurrent sedimentation patterns (Hardage et al, 1996b). The deformation in the deformed suprastratal zone consists of normal, reverse, and cylindrical faults and fractures (Loucks, 1999;McDonnell et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…The overlying strata were generally lithified, but the sag also affected concurrent sedimentation patterns (Hardage et al, 1996b). The deformation in the deformed suprastratal zone consists of normal, reverse, and cylindrical faults and fractures (Loucks, 1999;McDonnell et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…It is also unclear how tectonic movement and paleoclimate affected the architecture of sequences in the Central subbasin. Lowaccommodation settings are attractive targets for hydrocarbon exploration, but in such settings, reservoir development is notoriously unpredictable and reservoirs are internally complex and commonly strongly compartmentalized (Hardage et al, 1996). A better understanding of how strata formed in low-accommodation conditions could have considerable potential for predicting the presence of hydrocarbons (Allen and Fielding, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (1997) suggested that more than 200 seismic attributes (not all of them are independent) would be useful in constructing reservoir depositional model. Other researchers (Horkowitz, et al, 1996;Hardage et al, 1996b;Cooke, et al, 1999) claimed that instantaneous frequency and/or instantaneous phase are effective at highlighting facies changes. Similarity analysis based on multiple point-based attributes, their means and deviations was used to map seismic facies (Michelena, et al, 1998).…”
Section: Well-based Depositional Modelmentioning
confidence: 99%
“…However, these studies were mainly focused on the entire Fort Worth Basin. Hardage et al (1996b;1996c) and Carr et al (1997) analyzed the reservoir distribution and depositional subfacies using a few typical wells from this study area, but their model is not sufficiently detailed to be useful for facies analysis of this thin Caddo sequence. In addition, the tight non-reservoirs were generally not studied even though both the limestones and reservoir sandstones exist and appear seismically similar in the Boonsville Field.…”
Section: Well-based Depositional Modelmentioning
confidence: 99%
See 1 more Smart Citation